THE USE OF TYPES OF KUPNAT IN ADULT WOMEN'S CLOTHING TO EXPLORE COOPERATIVE METHODS AND PATTERN BREAKING EXERCISES IN PATTERN AND SEWING LECTURES (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2024)
This study aims to improve the teaching process to students, in this study cooperative methods and exercises are used. The selection of this method is very suitable to facilitate the learning process and improve the easy way of teaching with this method. This method will improve student learning outcomes, because by working together to design a pattern of difficulties faced will be easily solved together in the group, after that it is expected to be able to carry out exercises to facilitate, and their abilities will continue to increase in accordance with the competencies and targets that have been set. The pattern breaking method applied is the pivot method and the slash method. The pivot method is a pattern breaking method, by moving the cupnats to various corners following the design, so that they become decorative lines such as cup, princess, empire, yoke and so on. While the slash method is a polishing / pattern breaking design system by cutting certain parts to increase the distance that is useful for making wrinkles, smooth pleats or decorative lines. Like the model in the pivot method. In addition to data on the value of learning outcomes, interviews were also conducted, to strengthen the answers to the positive tendencies that have been obtained in learning using cooperative methods and exercises. This learning target and the results of the interviews have mutually supported the success of learning during the research. Key words : Design pattern, pivot method, slash method